Academic Interest Scale for Adolescents: Development, Validation, and Measurement Invariance With Chinese Students - Luo, Zheng; Dang, Yun; Xu, Wenjie (Frontiers in Psychology, 2019)
Hidi and Renninger’s four-phase interest development model was identified as the most complete and widely used theoretical model illustrating the essence of academic interest. Using the model along with current research literature as a basis, this study aimed to develop and initially validate a generic multidimensional instrument to measure academic interest across different school subjects in the Chinese education context; this instrument was called the Academic Interest Scale for Adolescents (AISA). Three large samples of Chinese junior high school students were recruited by cluster sampling in the study. (1) Sample 1 (N = 552; 45.5% girls; 12.31 [SD = 0.98] years, range = 10–15 years) completed the draft of AISA, Intrinsic Motivation Scale and Scale for Adolescents’ Flow State in Learning in math and English. (2) Sample 2 (a subgroup of Sample 1, 411 students) completed the AISA in math and English again 2 months later after the first survey. (3) Sample 3 (N = 1,780; 50.1% girls; 13.69 [SD = 0.97] years, range = 12–16 years) completed the AISA in math, English, and Chinese. Identically worded items were used in AISA, except for the name of the subject. An exploratory factor analysis for math in sample 1 using principle axis factoring and promax rotation resulted in a 29-item AISA containing four dimensions: emotion, value, knowledge, and engagement, and the latent variables together explained 59.40% of the total variance. Confirmatory factor analysis for math, English, and Chinese in sample 3 suggested the four-factor model fits well in different samples and subjects. Scale scores showed adequate internal consistency (the Cronbach’s α for AISA and each subscale ranged from 0.86 to 0.93) and acceptable test-criterion relationships (correlations between the AISA score and intrinsic motivation and flow state in learning > 0.51, ps < 0.001). Furthermore, the structural measure invariance across subjects, time (2-month interval), genders and grades were upheld. The AISA promises to be a useful tool for the evaluation of academic interest among Chinese adolescents and can be administered in different educational settings, i.e., different subjects, time, genders, and grades.